Leadership Accountability in a Globalizing World - Williams, C. author. aut Link
XI, 270 p.
Keywords: Leadership accountability - for violence, corruption and environmental harm - is a new aspect of globalization and civil society. This innovative forward-looking analysis explains how 'cumulative lock-in' fuels leadership deceit. The lessons are for those learning to be, or learning to question, leaders.